Analisys of half-squat mechanical specificity to track and field throwing techniques - Coimbra, H.; Vaz, M.; Ramos, N.; Fernandes, J.; Carvalho, J.; Conceicao, F. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to measure and compare the leg kinematics and kinetics of half-squats with a large spectrum of loads and three different track-and-field throwing actions (hammer, discus and javelin throws). One experienced thrower of each discipline was selected. Knee angular velocity, knee angle and vertical ground reaction force were measured for the half-squat and the throwing techniques. The results suggested that this method allows training loads to be selected for the half-squat that are more specific to the individualized performance of each leg.